Prognosis of ovarian cancer is associated with effector memory CD8+ T cell accumulation in ascites, CXCL9 levels and activation-triggered signal transduction in T cells. (4th May 2018) - Lieber, Sonja; Reinartz, Silke; Raifer, Hartmann; Finkernagel, Florian; Dreyer, Tobias; Bronger, Holger; Jansen, Julia M.; Wagner, Uwe; Worzfeld, Thomas; Müller, Rolf; Huber, Magdalena
ABSTRACT: The accumulation of intratumoral CD8 + T cells is associated with the survival of high grade serous ovarian carcinoma patients, but it is unclear which CD8 + T cell subsets contribute to this effect and how they are affected by the peritoneal tumor microenvironment. Here, we provide evidence for a functional link between long relapse-free survival, accumulation of CD8 + effector memory T (TEM ) cells in peritoneal effusion (ascites), and the level of the CD8 + TEM attracting chemokine CXCL9, produced by macrophages as a major source. We also propose a novel mechanism by which the tumor microenvironment could contribute to T cell dysfunction and shorter survival, i.e., diminished expression levels of essential signaling proteins, including STAT5B, PLCγ1 and NFATc2. CD8 + TEM cells in ascites, CXCL9 levels and the expression of crucial signal transduction proteins may therefore be important biomarkers to gauge the efficiency of immune therapies and potentially represent therapeutic targets.